The psychological and social benefits of a nature experience for children: A preliminary investigation. (June 2019) - Dopko, Raelyne L.; Capaldi, Colin A.; Zelenski, John M.
Abstract: There are active movements to connect children with nature to improve their well-being. However, most of the research on children and nature has focused on cognitive benefits or used non-experimental designs. In a preliminary study, we examined the potential benefits of a 4-hour nature experience on children's mood, pro-sociality, and attitudes toward nature. Eighty students from an urban Canadian elementary school were recruited to participate in field trips to a nature school and an aviation/space museum. Children reported more positive and negative emotions, a closer connection to nature, and a greater willingness to protect nature when at the nature school. We also found indications that children were more pro-social at the nature school. Although further research is needed to replicate these findings with additional populations/environments, this study suggests that children largely benefit from spending time in nature. Highlights: To examine potential well-being benefits, children attended a nature school. Children reported more positive and negative emotions, and a closer connection to nature. Children were also more pro-social at the nature school.